Correlation of Ferritine and Brain Derived Neurotrophic Factor (BDNF) Levels in Preeclampsia - Dona Mirsa Putri; Ariadi Ariadi; Yusrawati Yusrawati (Andalas Obstetrics And Gynecology Journal, 2021)
Iron deficiency anemia that followed by low serum ferritin levels in early pregnancy has an indirect impact on decreasing the expression of Brain Derived Neurotrophic Factor (BDNF) in the maternal hippocampus. BDNF together with its receptor tyrosine kinase B (TrkB) induced the expression of metalloproteinase-9 (MMP-9) which plays an important role in blastocyst implantation, trophoblast invasion and placental development. Decreasing BDNF levels can interfere with those process which caused imbalance of pro-angiogenic and anti-angiogenic factors such as VEGF, PIGF, sFlt1 and sEng that leads to preeclampsia. This study aims to determine the correlation between ferritin and BDNF serum levels in preeclampsia.Keywords: Preeclampsia, ferritin, iron deficiency anemia, Brain Derived Neurotrophic Factor